2020
DOI: 10.4103/jfmpc.jfmpc_458_20
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of cardiovascular disease associated risk factors among Saudis in Riyadh City

Abstract: Objective: The aim of this study was to estimate the awareness of Saudi population in Riyadh regarding cardiovascular diseases (CVDs) and their risk factors. Methods: This was a cross-sectional study that used self-administered questionnaires conducted in universities, primary care centers, and electronic copies distributed in social media websites. Results: Overall, 47.1% of the respondents had a good awareness of CVD and associated risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 29 publications
4
15
1
Order By: Relevance
“…Family history of CVD, dyslipidemia, hypertension, and diabetes was less frequently identified by participants as risk factors for developing CVDs. These results are congruent with those of studies conducted in Saudi Arabia (Alghamdi et al, 2021; Mujamammi et al, 2020), Kuwait (Awad & Al-Nafisi, 2014), and Jordan (Mukattash et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Family history of CVD, dyslipidemia, hypertension, and diabetes was less frequently identified by participants as risk factors for developing CVDs. These results are congruent with those of studies conducted in Saudi Arabia (Alghamdi et al, 2021; Mujamammi et al, 2020), Kuwait (Awad & Al-Nafisi, 2014), and Jordan (Mukattash et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…A combination of unhealthy diet and lack of exercise are the main reason behind overweight and obesity. Mujamammi et al (2020) conducted an awareness study of CVDs associated risk factors among Saudis in Riyadh city and have reported that the most factors were unhealthy diet, smoking, dyslipidemia, and physical inactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a few of the respondents recognized the most common heart attack symptoms (i.e., jaw and neck pain). Similarly, respondents in previous studies in Riyadh (Mujamammi et al, 2020) and Cameron (Aminde et al, 2017) reported shortness of breath as a heart attack warning symptom. Other significant symptoms, such as pain in the left arm or shoulder, pain in the jaw, weakness, or light-headedness, were identified only by a minority of the respondents, similar to a previous study (Aminde et al, 2017).…”
Section: Discussionmentioning
confidence: 69%
“…The researchers developed a three-section questionnaire after an extensive review of relevant literature (Alotaibi et al, 2018;Aminde et al, 2017;Awad & Al-Nafisi, 2014;Mujamammi et al, 2020). First section: Background Data Sheet It consisted of 13 items related to sociodemographic and biomedical data of the study sample.…”
Section: Instrumentsmentioning
confidence: 99%
“…Despite the awareness, all the smokers (100%) in this study continue to smoke. A recent study done in the city of Riyadh among Saudi citizens showed that approximately 75% of the participants considered smoking as a risk factor for CVDs (Mujamammi et al, 2020). The prevalence of CVDs in Saudi Arabia is rising, and tobacco smokers are at increased risk of suffering from morbidities and mortalities related to it (Alhabib et al, 2020).…”
Section: Resultsmentioning
confidence: 99%